A Personal Word - Cooke, Francis; Cooke, Francis (Victoria University of Wellington Law Review, 2008)
This article is a son's tribute to his father, Lord Cooke of Thorndon. The article describes Lord Cooke's personal attributes, and how they influenced his approach to legal problems and judging. The author states that an analysis of his father's judicial and extra-judicial work demonstrates that he was frequently concerned with attempts to explain why particular verbal formulations which had become reasonably well-settled were hiding rather than exposing the underlying principle. The author explores his father's take on the Wednesbury unreasonableness test as well as other general areas of law including tort and constitutional measures.